The Correlation between Discipline and Work Productivity at PT. Bina Megah Indowood - Devy Syanindita Roshida; Indriati Paskarini (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Productive human resources are able to complete the given tasks and responsibilities well. Discipline is the mental attitude at work needed to achieve productivity. Discipline at work creates smooth operational activities of the company. PT. Bina Megah Indowood is a manufacturing company that provides solid wood flooring with various thickness. The present study analyses¬ the correlation between individual characteristics, discipline, and work productivity among molding machine workers of PT. Bina Megah Indowood. Methods: This study was an observational analytic study with a cross sectional approach. Variables in this study were work discipline as an independent variable and productivity as a dependent variable. The population in this study were 58 workers in the molding section, 50 of whom were taken as samples. The sampling technique used was a simple random sampling. Morover, the two types of data used in this study were primary data obtained from questionnaires and secondary data obtained from the company profiles and a summary of production results every month. The technique of data analysis data was a Spearman correlation test. Results: Most workers in the molding machine production unit of PT. Bina Megah Indowood have moderate discipline and moderate work productivity. There is a correlation between discipline and work productivity with ρ-value = 0.020. The contingency coefficient between discipline and work productivity is 0.328, which means the correlation is weak. Conclusion: Higher work productivity is followed higher level of discipline. Meanwhile, individual characteristics have no correlation with work productivity because the distribution resultof individual characteristics is only dominant in one category.Keywords: discipline, individual characteristics, work productivity